FAKTOR INTERNAL DAN EKSTERNAL PEMBELAJARAN - Parni Parni (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2017)
Factors that influence the learning process do not only come from students themselves but also come from outside. This is very closely related between one factor and another, because if the two factors are not continuous then the learning process will not run smoothly and the results obtained will not be optimal. Keywords: Internal, external, learning factors.